Influência da redução a frio e da microestrutura e da textura iniciais na microestrutura, textura e propriedades de um aço inoxidável ferrítico estabilizado ao nióbio - Daniella Gomes Rodrigues (2017)
The present work investigates the effect of the cold rolling, microstructure and the initial texture of the hot rolled band and intermediate annealing between cold rolling passes on the deformation texture, recrystallization, recrystallization texture and mechanical properties of niobium stabilized ferritic stainless steel, type ASTM 430. The samples were cold rolled with 50%, 60%, 80%, 85% and 90% thickness reduction from the hot rolled band. From the intermediate hot rolled band, the samples were cold rolled with 50%, 63% and 80% of thickness reduction. These reductions were carried out in samples with different grain size. The annealing was interrupted at 750 °C, 800 °C, 850 °C, 880 °C and after 24 s of soaking time at 880 °C. As the thickness reduction increased, there was an increase in energy stored energy of cold word, in the fraction of the -fiber and in the {111} <011> component. The previous average grain size did not influence the development of the -fiber in the deformation texture. On the other hand, the initial texture directly affected a deformation texture. The samples with intense fiber in the hot rolled band showed the strong -fiber after the cold rolling. The samples with -fiber before cold rolling showed -fiber after deformation, and it was increased continuously with deformation. After recrystallization, the increase in the reduction resulted in the increase of the -fiber fraction and the reduction of the fiber {110} parallel of planes of the sheet, especially in the previous fine grained samples. However, the -fiber was not strongly influenced by the increase of the reduction and the previous grain size. The yield strength, tensile strength and elongation were not strongly influenced by initial characteristics of the hot rolled band, by the increase of the cold rolling and insertion of the intermediate annealing. The average normal anisotropy coefficient, , enhanced with a reduction of the grain size of the initial samples and by the insertion of the intermediate annealing. However, the planar anisotropy coefficient, r, was reduced with the increase of the cold rolled and increased with an insertion of the intermediate annealing. A highest -value of 1.92 for deep drawing operation was obtained for a / ratio of 8.12 in the sample with previous fine grain size and with the insertion of intermediate annealing.